Urban Management in Authoritarian China: How the Smart City is Used to Enhance Comprehensive Law Enforcement. - Tsai, Wen-Hsuan; Lin, Ruihua; Wang, Hsin Hsien (Journal of Contemporary China, 2024)
'Comprehensive law enforcement' is an important part of the Chinese Communist Party's (CCP's) thinking on urban management. It involves all government departments and units related to law enforcement working together to improve their administrative efficiency. Since 2009, the CCP has absorbed some elements of the Western concept of the 'smart city', including the use of big data analysis and technology in implementing and enforcing the law. At the heart of the Chinese smart city is the 'city brain'. For the CCP regime, the primary purpose of the smart city is to monitor society and improve the efficiency of urban management; making life more convenient for residents is a secondary consideration. In other words, this mechanism is strongly state led in nature, and it is aimed at ensuring the regime's survival by strengthening the CCP's capacity to govern. We found that due to incentives built into the cadre evaluation system, grassroots officials use the information gathered through smart city technology to achieve 'hard' law enforcement targets rather to improve people's lives.